Exosomal let-7b-5p derived from Aspergillus fumigatus-treated human corneal epithelial cells promotes M1 macrophage activation via targeting SOCS-1 - Yu, Xiaoming; Wu, Xinyi (Frontiers in Immunology, 2025)
PurposeThis study aimed to explore the impact of exosomal miRNAs derived from Aspergillus fumigatus (A. fumigatus)-treated human corneal epithelial cells (HCECs) on M1 macrophage activation. We further clarified the mechanisms contributing to M1 macrophage activation in fungal keratitis.MethodsExosomes were harvested from A. fumigatus-treated HCECs. Transmission electron microscopy, particle size analysis, and western blotting were performed to identify exosomes from HCECs. A laser confocal microscope was used to trace the exosomes. Macrophages were incubated with exosomes derived from A. fumigatus-treated HCECs. Global miRNA expression profiling of exosomes was assessed by high-throughput differential gene expression analysis. PCR and western blotting were used to detect the expression of M1-related proteins and SOCS-1. PCR was performed to detect the expression of pro-inflammatory cytokines and let-7b-5p. A dual-luciferase reporter assay was used to confirm the direct targeting of let-7b-5p.ResultsA. fumigatus-treated HCEC-derived exosomes notably promoted M1 macrophage activation and the production of inflammatory cytokines. Let-7b-5p was overexpressed in exosomes. Let-7b-5p inhibitors suppressed the M1 immune response induced by exosomes. Overexpression of let-7b-5p repressed the expression of SOCS-1, whereas the let-7b-5p inhibitor dramatically increased the expression of SOCS-1. Moreover, a dual-luciferase reporter assay confirmed that SOCS-1 is a direct target of let-7b-5p.ConclusionsLet-7b-5p is secreted by A. fumigatus-treated HCECs and transferred to macrophages via exosome secretion. The communication between A. fumigatus-treated HCECs and macrophages was facilitated by exosomal let-7b-5p, resulting in the activation of M1 macrophages. The exosome/let-7b-5p/SOCS-1 axis is vital for innate immunity against fungal keratitis and provides insights into the molecular mechanisms involved in this condition.